Pharmacist counseling improves medication compliance of schizophrenia patients - Pranata, Meki; Perwitasari, Dyah Aryani; Noerhidayati, Elly; Iskak, Iskak; Darmawan, Endang; Angella, Widi (Universitas Ahmad Dahlan, 2025)
Schizophrenia is a disorder characterized by abnormal behavior, impaired thinking, disorganized speech, and a reduced ability to perceive reality. One of the key factors influencing the success of schizophrenia therapy is patient adherence. Pharmacy plays a crucial role in the treatment of schizophrenia patients. This study aimed to determine the effect of pharmacist counseling on drug adherence of schizophrenia patients from the first month to the second month. The method used in this study was a one-group pre-test and post-test design that used quasi-experimental research. The subjects of this study were schizophrenia patients in the outpatient installation of Prof.Dr.Soerojo Mental Hospital, Magelang. This study used the Medication Adherence Rating Scale (MARS) questionnaire to measure the level of adherence and drug use monitoring sheet (pill count) to monitor the amount of patient medication. The population in this study was calculated using the Lameshow formula. Data analysis was performed using the chi-square test and the Wilcoxon test. After analyzing data of 108 patients, it was found that there was a significant difference between before and after counseling conducted by pharmacists on medication adherence in schizophrenia patients, with a significance value of p <0.05. Counseling conducted by pharmacists has a good impact on patient medication adherence and monitoring the amount of medication taken. These results indicate the effect of counseling conducted by pharmacists on adherence to taking medication and the monitoring of the amount of medication taken by patients.